Leadership self-efficacy and organizational commitment of faculty members: Higher education - Yousef Mubrik N. Almutairi (Administrative Sciences, 2020)
Education is one of the means of achieving sustainable development. Universities are responsible for training and generating skilled personnel needed in attaining holistic development; to accomplish the goals for which universities were established, effective leadership is required. The beliefs upheld by leaders about their ability to accomplish targets and deliver as expected is an indispensable constituent of university administration. Therefore, this research study examined connections between leaders' self-efficacy and faculty members' organizational commitment in Saudi Arabian universities. Therefore, 400 faculty members were randomly selected from three different public universities in the central, south-western and northern part of the country. Using the Pearson product correlation coefficient, it was found that positive connection occurs amongst leaders' self-efficacy and affective commitment. Additionally, there is a positive association among leaders' self-efficacy and continuance commitment. Leadership self-efficacy has a positive connection with normative commitment. In order to improve organizational commitment of faculty members, leaders must step up their self-efficacy and provide an enabling environment for team work and innovation.
Keywords: 350; faculty members; leadership; organizational commitment; self-efficacy; universities